The Relation between Unemployment Rate and Economic Growth in USA - Roșoiu, Iulia; Roșoiu, Andreea (International Journal of Economic Practices and Theories, 2014)
The relation between unemployment rate and gross domestic product for the economy of United States of America is important to be analyzed, especially in the context of the current financial crisis. The relation between these two variables is known in the economic literature as Okun’s Law. According to this law, during recession periods, the unemployment rate has a stronger reaction to a certain variation in gross domestic product evolution. On the other hand, the unemployment rate keeps its value around a natural level during economic upswings periods. The results obtained from the regression between unemployment rate and economic growth over the period 1977-2011 show that these variables respect the relation described by Okun’s Law. Moreover, the evolution of the unemployment rate is also influenced by other factors which are not included in the analysis.